Innovative Strategies of Change Management in the Indonesian Banking Industry in an Election Year - Ridhovan, Andreanov Ridhovan; Anggarani, Ari (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to analyze innovative change management strategies applied by the Indonesian banking industry in facing the challenges arising during election years. Through a qualitative approach and data collection from various primary and secondary sources, including interviews with bank representatives and analysis of public documents, this study explores the specific steps taken by Indonesian banks to adapt to the political and economic dynamics associated with elections. The findings indicate that Indonesian banks adopt diverse innovative strategies, including an increased focus on digital banking business, strengthening collaboration among banks, and accelerating digital transformation. Additionally, banks enhance risk management capacities, engage in economic and social development initiatives, and focus on sustainability and good corporate governance as part of their responses to the challenges encountered during election years. The implications of these findings are that Indonesian banks play a significant role in supporting national economic and financial stability as well as sustainable economic growth.